Four new genera and six new species of lyophylloid agarics (Agaricales, Basidiomycota) from three different continents - van de Peppel, Lennart J. J.; Aime, M. Catherine; Læssøe, Thomas; Pedersen, Ole S.; Coimbra, Victor R. M.; Kuyper, Thomas W.; Stubbe, Dirk; Aanen, Duur K.; Baroni, Timothy J. (Mycological progress, 2022)
Four new genera encompassing six new species are described in the Lyophyllaceae ( Agaricales ): the monotypic Australocybe from Australia; the monotypic Phaeotephrocybe from Belize; the monotypic Nigrocarnea from Laos containing the novel conidia-producing species N. radicata and Praearthromyces containing two Asian taxa, the conidia-producing P . corneri known from Malaysia and Singapore and P . griseus from Thailand, which lacks conidial production. In addition, we describe Arthromyces glabriceps , which is the first species in the genus Arthromyces that lacks conidial production on the basidiome. Alternative options for a classification of these lyophylloid taxa are discussed and based on morphological, ecological and biogeographical considerations rejected.